Menganalisis Bagaimana Indonesia Menyusun Anggaran Untuk Menentukan Penerimaan Dan Pengeluaran Negara - Danendra Bramantyo; Dinda Widya Kumala; Muhammad Yasin (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This research aims to analyze the budget preparation process in Indonesia, with a focus on how the government determines state revenues and expenditures. This study explores the mechanisms used in budget planning, including top-down and bottom-up approaches, as well as the role of various government agencies in the process. Data was obtained through analysis of budget documents, interviews with relevant government officials, and literature review. The research results show that budget preparation in Indonesia involves various complex stages and requires coordination between various parties. This research also found that although there are challenges in the transparency and accuracy of revenue projections, improvement efforts continue to be made through fiscal policy reform and improving financial information systems. Thus, this research provides important insights for policy makers and academics about the dynamics of budget preparation in Indonesia.